Design and Fabrication of an Automated Water-Jet Robot for PV Panel Cleaning Using an Arduino-Assisted HC-05 Bluetooth Module - Ramisetty Umamaheswari; Yeluri Sai Sanjana; Guntreddi Ritendra Kumar; Rayapureddi Dileep Naidu; Appana Sai Shashank; Eti Venkata Sai Shashank; Navara Pavan Manikanta Srinivasa Rao (Engineering Proceedings)
In the current scenario, renewable energy resources play a vital role in developing countries. Photovoltaic panel-based power plants have great significance for the production of electrical energy, due to automated transitions, easy interaction, and low maintenance costs. The energy-production efficiency depends on various factors and environmental effects. The formulation of a thin layer of dust particles on solar panels diminishes their energy-production capacity due to the limiting of heat transfer to the semiconducting materials. The current paper deals with the design and fabrication of an automated water-jet-assisted robot used to clean the dust particle layer and bird droppings on PV panels. In the water-jet-assisted cleaning robot, there is a two-brush mechanism that works in concert with the rover’s movement. A Bluetooth communication system plays a vital role by controlling the rover; this approach offers a perspective on a rover constructed with an Arduino-UNO micro-controller, along with an HC-05 Bluetooth sensor.